Topological properties and matrix transformations of certain ordered generalized sequence spaces - Manjul Gupta; Kalika Kaushal (International Journal of Mathematics and Mathematical Sciences)
In this note, we carry out investigations related to the mixed impact of ordering and topological structure of a locally convex solid Riesz space (X,τ) and a scalar valued sequence space λ, on the vector valued sequence space λ(X) which is formed and topologized with the help of λ and X, and vice versa. Besides,we also characterize o-matrix transformations from c(X), ℓ∞(X) to themselves, cs(X) to c(X) and derive necessary conditions for a matrix of linear operators to transform ℓ1(X) into a simple ordered vector valued sequence space Λ(X).